LOOKING FOR (LESBIAN) LOVE: SOCIAL MEDIA SUBTEXT READINGS OF RIZZOLI AND ISLES - Hemphill, Libby (AoIR Selected Papers of Internet Research, 2015)
Using Fiske’s (1989) semiotic supermarket metaphor, I examine how Twitter users mix and match moments from Rizzoli and Isles to create a coherent lesbian subtext. To do so, I use tweets containing the portmanteau hashtag #Rizzles or the related tag #Gayzzoli posted during two different episodes of the show. Live tweeting affords us an opportunity to eavesdrop on viewers’ listening activities and provides data useful for testing theories about reading/viewing and participation. Here, I demonstrate the utility of analyzing live tweeting and provide examples of how live tweeters publicly read resistant subtexts. Fiske (1987) argues that readers are able to assemble their own texts from television works by “’[listening’] more or less attentively to different voices” within the work (95). Though he didn’t introduce the term semiotic supermarket until later (Fiske, 1989), Fiske does provide a semiotic framing that is useful for analyzing social media readings of television texts. For instance, he argues that viewers exploit contradictions within the texts to locate their own social identities within the text (Fiske, 1986). I argue that we should understand the lesbian subtext reading of Rizzoli and Isles as precisely this kind of polysemic reading. I show how #Rizzles readers locate their own social identities within the text of the show and then use social media to share those locations with others publicly.